Measuring the economic relationship between economic ‎growth and industrial production in Algeria During the ‎period ‎ ‎(1970-2014) - testing a hypothesis Kaldor‏ -‏ - Hicher, Ahmed Tidjani (Dirassat Journal Economic Issue, 2017)
We thought of this study was to measure the economic relationship between the GDP and index of industrial production IND in Algeria during the period 1970-2014 by testing the hypothesis Kaldor, co-integration test results showed the presence of a long-run equilibrium relationship between GDP -IND, and depending on the outcome of causality tests conclude the existence of a one-way from GDP to IND causal relationship in the short and long term, helping to changes in industrial output and GDP in the interpretation of changes in industrial production in Algeria, these results reflect the role of economic growth in determining the rate of industrial production.